Pembuatan Aplikasi Entry Data Menggunakan Java Desktop (GUI) di SDN 1 Sukatani (Current Research in Education: Conference Series Journal, 2023)
The rapid development of technology affects every aspect of human life. Service and data management at SDN 1 Sukatani still uses the manual method, namely entering data for teaching staff and students so that it is less effective and efficient. The purpose of this research is to design, develop, and implement a data entry application to assist the data management process for teaching staff and students by implementing the data using an information system based on Java Netbeans IDE. The design of this data entry application uses the System Development Life Cycle (SDLC) development method with a prototyping model. Using Netbeans IDE 12.3 software in the programming process using the Java programming language and using phpMyAdmin for the database and using the Jar2Exe Wizard 2.5 application to convert from programming language to android application form as a tool for making data entry applications. In this desktop-based data entry application research, it is hoped that it can help the school at SDN 1 Sukatani in carrying out the process of finding data, entering data, and changing data for educators and students, educators and students.